Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1128/aem.41.3.646-651.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of activated carbon and bacteriostatic filters on microbiological quality of drinking water

Abstract: Three activated carbon filters for point-of-use water treatment were tested in laboratory and field studies for chemical removal and microbiological effects on water. All removed free available chlorine in municipally treated water to below the limit of detection, but removed only about 50 to 70% of the total available chlorine and 4 to 33% of the total organic carbon. Standard plate count bacteria in the effluent increased steadily with time for 3 weeks and remained elevated over the 8-week period of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Micrococcus and Bacillus predominate in the laboratory air (Corry et al 1986). In the present study the organisms were not identified at species level, however we agree with Smidt-Loren (1976) and Tobin (1981) that is important to know the predominant species in order to identify potential risks derived by bottled mineral water consumption and post-extraction contamination which contravenes the European Directive.…”
Section: Resultssupporting
confidence: 85%
“…Micrococcus and Bacillus predominate in the laboratory air (Corry et al 1986). In the present study the organisms were not identified at species level, however we agree with Smidt-Loren (1976) and Tobin (1981) that is important to know the predominant species in order to identify potential risks derived by bottled mineral water consumption and post-extraction contamination which contravenes the European Directive.…”
Section: Resultssupporting
confidence: 85%
“…In addition, this treatment is recognized as an effective process for removing naturally occurring organic material formed by the breakdown of animal and vegetable matter in the environment. Nevertheless, this process can result in bacterial colonization of GAC,1–10 which is considered to result in part from: (1) the adsorptive properties of carbon, which enrich nutrient and oxygen concentrations and remove disinfectant compounds; (2) the porous surface of the carbon particles, which provides a protective environment from fluid shear forces; (3) the presence of a variety of functional groups on the carbon surface, which enhances microbial attachment; and (4) neutralization of stressor compounds. Consequently, the bacteria attached to carbon particles are highly resistant to disinfectants 5.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the scanning electron microscopy examination of a slice of the SBAC did not reveal any evidence of significant bacterial colonization of its outlet and inlet surfaces (see photograph on page E295). These results were unexpected because early work had shown that carbon‐based devices are colonized by biofilm (Tobin et al, 1981). Also, on the basis of large HPC increases (up to 4 log) in effluent, Daschner et al (1996) concluded that significant biofilm is rapidly established (< 3 days), both in laboratory‐ and field‐installed POU devices and warned of their potential health effects.…”
Section: Resultsmentioning
confidence: 98%
“…Another accelerated pilot study (Deshommes et al, 2010a) conducted on under‐the‐sink POU devices up to 120% of their prescribed capacity revealed that total Pb levels were reduced adequately and that particulate Pb was removed more efficiently than dissolved Pb. One concern about POU devices is the bacterial colonization of their media because culturable bacteria could proliferate on activated carbon filters and therefore potentially aggravate the quality of POU effluent water (Tobin et al, 1981). Su et al (2009) showed indevice and post‐device colonization by heterotrophic plate counts (HPCs) during an accelerated laboratory study on carbon block POU devices, with accumulation of biofilm in dead‐end spaces.…”
mentioning
confidence: 99%